Transparent and tough poly(2-hydroxyethyl methacrylate) hydrogels prepared in water/IL mixtures - Liu, Yu-wei; Wang, Ping; Wang, Jun; Xu, Bo; Xu, Jin; Yuan, Jiu-gang; Yu, Yuan-yuan; Wang, Qiang (New journal of chemistry, 2020)
Poly(2-hydroxyethyl methacrylate) (PHEMA) hydrogels with high transparency and excellent mechanical properties are fabricated via in situ free radical polymerization of 2-hydroxyethyl methacrylate (HEMA) in mixtures of water and 1-butyl-3-methylimidazolium chloride (BmimCl) followed by the exchange of BmimCl with water. Compared with the PHEMA hydrogels prepared without BmimCl, the obtained hydrogels display a denser and more homogeneous microstructure, which contributes to their highly transparent appearance and outstanding mechanical properties. The hydrogels could achieve elongation at break and tensile strength up to 705% and 173 kPa, respectively, at swollen equilibrium states. Furthermore, the hydrogels also reveal fast recovery in water after circle elongation, showing anti-fatigue properties owing to their quick reformation of hydrogen bonds between polymer chains. More importantly, the hydrogels are able to retain considerable mechanical strength in water over a wide pH range (1 to 13) due to their stable cross-linking structures. It is believed that this novel type of transparent PHEMA hydrogel exhibiting outstanding mechanical properties, superior stability and anti-fatigue properties would find extensive applications in biomedical and industrial fields.